Race and the probability of pleading guilty - Albonetti, Celesta Ann (Journal of quantitative criminology, 1990)
The legal ramifications of pleading guilty and findings of an interdependence between pleading guilty and sentence severity suggest that the guilty plea decision is a significent turning point in case processing. The present research examines the variables affecting the probability of pleading guilty. The first analysis involves estimating a single probit equation of main effects of variables previously found to be related to pleading guilty. A second analysis is conducted estimating the same equation separately for black defendants and white defendants. Findings from the first part of the analysis indicate that physical evidence, number of charges, and confessing to the crime during police/prosecutor interrogation increase the probability of pleading guilty, whereas the number of witnesses, use of a weapon, and offenses carrying a minimum penalty of 5 years in custody with no maximum prison term decrease the probability of pleading guilty. Findings from the second analysis indicate that the effect of marital status, prior record of felony convictions, type of counsel, number of charges, and use of a weapon on the probability of pleading guilty varies by defendant's race. The research concludes by offering several competing explanations of these findings in hope of stimulating further research on the variables affecting the route of case disposition in felony processing.